The Prospects Of The Baltic-Black Sea Cooperation - Bykanov, D.D. (Культура народов Причерноморья, 2000)
The region from the Baltic to the Black Sea is situated in the very center of Eurasia (in geopolitical meaning you see, not geographic). It occupies the territories of 16 countries of the Central and Eastern Europe, the Caucasus and the Minor Asia.